2008
DOI: 10.1007/s12039-008-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent O···O interactions among isopolyanions using a cis-{MoO2} moiety by the assistance of N-H···O hydrogen bonds

Abstract: An inorganic-organic hybrid material, [2-AmpH] 4 [Mo 8 O 26 ](1) has been isolated by the reaction of Na 2 MoO 4 ·2H 2 O with 2-aminopyrimidine (2-Amp) from an acidic aqueous medium. In this low pH synthesis, the organic molecule (2-Amp) gets mono-protonated (2-AmpH + ) and acts as the cation in stabilizing the octamolybdate anion in 1. Compound 1 crystallizes in the triclinic space group P-1 with a = 9⋅925 (3) (4), β = 64⋅907(4), γ = 89⋅506(4)°, Z = 1. An interesting three-dimensional supramolecular structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…This partial deprotonation of diammonium ion has not been observed in any MMX chains synthesized so far. Although several kinds of compounds containing mono-protonated diamines as countercation have been reported [32][33][34][35][36], these compounds were synthesized from neutral diamines with acid. It should be noted that 1 differs from them in that it was synthesized from fully protonated diammonium, {o-(H 3 NC 6 H 4 NH 3 )}SO 4 , via the deprotonation.…”
Section: Resultsmentioning
confidence: 99%
“…This partial deprotonation of diammonium ion has not been observed in any MMX chains synthesized so far. Although several kinds of compounds containing mono-protonated diamines as countercation have been reported [32][33][34][35][36], these compounds were synthesized from neutral diamines with acid. It should be noted that 1 differs from them in that it was synthesized from fully protonated diammonium, {o-(H 3 NC 6 H 4 NH 3 )}SO 4 , via the deprotonation.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to the intermolecular O•••O interactions, they were mainly identified within electron densities of crystal structures. For instance, Bianchi et al [8] found an intermolecular O•••O contact (OÀ O distance shorter than the sum of the van der Waals radii) between Mn 2 (CO) 10 complexes in metallo-carbonyl crystals through an accurate X-ray diffraction analysis at 120 K. Besides, Arumuganathan et al [9] also reported a close O•••O contact between polyoxometalate moieties of cis-{MoO 2 } complexes. In another QTAIM study on the crystal structure of dinitrogen tetroxide, Tsirelson et al [10] have found that the multiple O•••O interactions between N 2 O 4 molecules can also be characterized as "hole-lump" interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bianchi et al [8] . found an intermolecular O⋅⋅⋅O contact (O−O distance shorter than the sum of the van der Waals radii) between Mn 2 (CO) 10 complexes in metallo‐carbonyl crystals through an accurate X‐ray diffraction analysis at 120 K. Besides, Arumuganathan et al [9] . also reported a close O⋅⋅⋅O contact between polyoxometalate moieties of cis‐{MoO 2 } complexes.…”
Section: Introductionmentioning
confidence: 99%